Proposal and practice of software process improvement framework – Toshiba's software process improvement history since 2000. Issue 5 (4th February 2014) - Ogasawara, Hideto; Kusanagi, Takumi; Aizawa, Minoru; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
SUMMARY For the effective promotion of software process improvement (SPI) activities in a large organization, it is necessary to establish an organizational structure and a deployment method for promotion and to develop training courses, support tools, and other materials. Even if an organizational promotion system is established, the SPI activities of each development department cannot be promoted effectively without an SPI community. To promote SPI activities throughout Toshiba Group, we organized a Corporate Software Engineering Process Group in April 2000. We also proposed an SPI framework. This framework extracts the features of organizations in which improvement activities were successful in the 1990s and combines them systematically. For over 10 years, we have been constructing Toshiba's SPI framework based on the SPI framework that we proposed and promoting process improvement activities using it. As a result, maturity levels were improved in many development departments, and the applicability of the SPI framework has been confirmed. Copyright © 2014 John Wiley & Sons, Ltd.